Dinamika Naratif Film "Hati Suhita" Karya Khilma Anis - Syawalia, Laila; Ecca, Suleha; Mahmud, Nurlaelah; Kamal, Kamal (Nuances of Indonesian Language, 2024)
This research analyzes narratives in films and dissects them using theory according to Tzvetan Todorov. This research aims to describe the narrative at the beginning, middle and end of the film Hati Suhita. This research uses qualitative research methods with a narrative approach. Based on the results of research using Tzvetan Todorov's narrative analysis, namely the narrative from beginning to end in the film is very clearly structured starting from the beginning, middle and end plot. There are 6 initial equilibria, 4 disruptions and 4 re-settlements in this film. By using image codes, including minutes, and accompanied by conversational dialogue, researchers can obtain valid data. In the initial plot, things are still harmonious, it can be seen that Alina Suhita and Gus Birru's marriage is in good condition even though they both don't love each other. Then the middle plot of this film shows that conflict begins to emerge and the balance begins to be disturbed, the peak of the conflict occurs when Alina and Gus Birru argue which occurs because of the wishes of their parents who urge them to immediately have children. The final plot, namely the conflict finally ends, is seen when Gus Birru apologizes to Alina, resulting in the conflict ending and a final balance emerging. In accordance with the model described by Todorov, the initial plot of this film is still in a normal state, balance begins to exist. Then the middle plot of this film explains how conflict begins to arise and the balance begins to be disturbed. The final plot is that the conflict finally ends and balance begins to occur.